Etiologies of endometriosis and model systems: is there a risk of a tunnel vision? - Manavalan, Mary Ann; Babtain, Mona; Weessies, Myrthe; Nap, Annemiek; Verdurmen, Wouter P. R.; Taurin, Sebastien; Sater, Mai; Brock, Roland (Frontiers in Medicine, 2025)
Endometriosis is the growth of endometrial-like tissue at non-uterine locations, primarily within the peritoneal cavity. The disease can have diverse presentations with superficial lesions, deep invading lesions and ovarian cysts (endometrioma) as the main subtypes. Immune dysregulation, recurrent inflammatory processes and fibrosis are commonalities of all endometriosis forms. Most theories explaining the etiology of endometriosis take their origin in retrograde menstruation. However, other theories have been proposed, including metaplasia of mesothelial tissue, abnormal proliferation of Müllerian duct embryonic tissue remnants and a stem cell origin. We here argue that there is a lack of attention on whether retrograde menstruation can equally explain the various forms of endometriosis or whether the different endometriosis subtypes differ in etiology. As we show, there is a strong case in favor of several etiologies, as retrograde menstruation alone would require too many assumptions for some clinical appearances of endometriosis. Specific histological and molecular signatures have been associated with the different proposed etiologies. However, these are not part of the standard histopathological characterization of an endometriosis lesion. In addition, current ex vivo model systems aim to reconstitute the overall histological structure of a lesion but do not address the potential consequences that different etiologies may have on function and response to therapy. We thus propose to rethink the current diagnostic approach and direct research more specifically toward the cellular and molecular mechanisms underlying the various proposed etiologies, which should then be reflected in ex vivo model systems.